2022
DOI: 10.3390/cells11020213
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Roles of the Chemokine Receptor ACKR3/CXCR7 in Platelet Pathophysiology

Abstract: The manifold actions of the pro-inflammatory and regenerative chemokine CXCL12/SDF-1α are executed through the canonical GProteinCoupledReceptor CXCR4, and the non-canonical ACKR3/CXCR7. Platelets express CXCR4, ACKR3/CXCR7, and are a vital source of CXCL12/SDF-1α themselves. In recent years, a regulatory impact of the CXCL12-CXCR4-CXCR7 axis on platelet biogenesis, i.e., megakaryopoiesis, thrombotic and thrombo-inflammatory actions have been revealed through experimental and clinical studies. Platelet surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 206 publications
(444 reference statements)
0
17
0
Order By: Relevance
“…Interestingly, treatment with ACKR3 agonist does not affect basal hemostatic or coagulation response. Thus, the anti-thrombotic actions of ACKR3 through the modulation of the platelet lipidome to limit metabolism and release of thrombotic and atherogenics mediators strengthened the therapeutic potential of ACKR3 in CVD ( 96 ). However, the mechanisms underlying this anti-thrombotic action of ACKR3 in platelets remain ascertained and further studies are needed.…”
Section: Ackr3 In Cardiovascular Diseasesmentioning
confidence: 99%
“…Interestingly, treatment with ACKR3 agonist does not affect basal hemostatic or coagulation response. Thus, the anti-thrombotic actions of ACKR3 through the modulation of the platelet lipidome to limit metabolism and release of thrombotic and atherogenics mediators strengthened the therapeutic potential of ACKR3 in CVD ( 96 ). However, the mechanisms underlying this anti-thrombotic action of ACKR3 in platelets remain ascertained and further studies are needed.…”
Section: Ackr3 In Cardiovascular Diseasesmentioning
confidence: 99%
“…Recently, the atypical chemokine receptor 3 (ACKR3), also known as CXC-chemokine receptor 7 (CXCR7), was shown to be expressed on platelets, modulating its function after binding of its endogenous ligand CXCL12 (also known as SDF-1; stromal cell-derived factor 1) and the subsequent recruitment of β-arrestin (Figure ). Recent studies found that surface expression of ACKR3 is upregulated on platelets in patients with acute myocardial infarction and that increased ACKR3 expression improves the recovery in patients after myocardial infarction. , On the contrary, endothelial ACKR3 deletion hinders recovery of heart function after myocardial infarction, leading to increased mortality and infarct size rates, which is linked to the receptors’ role in proliferation and angiogenesis . These findings suggest ACKR3 as a promising therapeutic target for platelet-mediated thrombosis or other specific cardiovascular conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, β-arrestin recruitment leads to inhibition of platelet aggregation, suppression of pro-thrombotic response, and induction of the platelets’ lifespan. On the contrary, CXCR4 activation on platelets triggers platelet activation, aggregation, and thrombus formation. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations